TYPE OF CODE MIXING FOUND IN PODCAST MD ENTERTAINMENT BY FREDERIKA CULL ON PODCAST YOUTUBE CHANNEL - Ayu Riantini, Ni Kadek (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Most Model in Indonesia use English mix with Indonesian language in their utterances. Therefore code mixing often can be seen there. This study aims to find out the type of code mixing found in Frederika Cull on Podcast YouTube Channel in the video podcast. The method used in this research is descriptive qualitative method. The analysis method is content analysis with the theory from Pieter Muysken (2000). The result of this study shows that code mixing used in the utterances of Frederika Cull. The dominant mixing is the type of Insertion.Â and the reason to this finding is this study show that a bilingual, Frederika Cull has high social values but still maintains her cultural identity and finds the language level that appears in code mixing.